2016
DOI: 10.1111/dmcn.13115
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of cerebral visual impairments in infants born extremely preterm

Abstract: RTFReaction time to fixation AIM Children born extremely preterm are at risk of visual processing problems related to brain damage. Damage in visual pathways can remain undetected by conventional magnetic resonance imaging (MRI) and functional consequences cannot always be predicted. The aim of this study was to assess the efficacy of processing visual information in infants born extremely preterm at a corrected age of 1 year using a communication-free visual function test based on eye tracking. METHOD RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In the present study, we focus on children born very or extremely preterm (i.e., born < 30 weeks of gestation) from 1 year of corrected age (CA). In an ongoing longitudinal study, we found elevated risks of visual attention and processing problems in this population [15,16], driving the urgency for interventions. However, we expect outcomes to be applicable to other young children at risk of brain damage-related VPD.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In the present study, we focus on children born very or extremely preterm (i.e., born < 30 weeks of gestation) from 1 year of corrected age (CA). In an ongoing longitudinal study, we found elevated risks of visual attention and processing problems in this population [15,16], driving the urgency for interventions. However, we expect outcomes to be applicable to other young children at risk of brain damage-related VPD.…”
Section: Introductionmentioning
confidence: 89%
“…There are no thorough estimates of the prevalence of VPD in preterm children. A previous study using the eye tracking-based assessment in extremely preterm children identified visual processing delays in 48% of preterm children without evidence for brain damage [16], and in 9% to 23% of children in a cross section of the preterm population at 1 year CA [15]. In addition, between 25% and 33% of children with CVI have prematurity as a contributing factor [32].…”
Section: Sample Size Calculationmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition to the reproducibility of individual differences, we examined whether these differences were associated with risk factors that are common in low‐resource settings, particularly preterm birth, but also malnutrition, and psychosocial risk factors. The possibility that infants early attentional behaviors are sensitive to these risk factors is suggested by previous studies in high‐resource settings showing slower visual orientation (Landry, Leslie, Fletcher, & Francis, ; Pel et al., ; Shah et al., ; however, see also Foreman, Fielder, Price, & Bowler, ; Hunnius, Geuze, Zweens, & Bos, ; Rose, Feldman, Jankowski, & Caro, for contrary evidence), slower attention shifts between two competing objects (Atkinson et al., ; Butcher, Kalverboer, Geuze, & Stremmelaar, ; de Jong, Verhoeven, & van Baar, ), and reduced attention to faces (Telford et al., ) in preterm infants. Further, various sources of evidence from high‐ and low‐resource settings point to poorer cognitive function in growth‐stunted children (Champakam, Srikantia, & Gopalan, ; Galler et al., ; Rose, ; Thompson et al., ) and in children raised in low socioeconomic status households (Hackman, Gallop, Evans, & Farah, ).…”
Section: Early Development Of Visual Attention In Infants In Rural Mamentioning
confidence: 99%